Relationship between different diet indices and frailty and mortality in population with CKD - Peng, Jing; He, Yuhan; Zhang, Bohua; Liao, Ruoxi; Su, Baihai (Frontiers in Nutrition, 2025)
BackgroundModification of diet is a convenient and cost-effective approach proven to be beneficial for populations with chronic kidney disease (CKD). Nutritional status is closely related to the frailty status, and both are associated with health outcomes. However, in populations with CKD, the prognostic value of different dietary indices for survival and how frailty will influence their association remains unclear. The objectives of our analysis were: (1) to assess the associations between frailty and seven dietary indices in the population with CKD; (2) to evaluate the mortality risk of frailty and different dietary scores in CKD; (3) to explore the association between dietary scores and mortality after adjustment for the frailty index.MethodsA total of 4,445 participants with CKD (aged ≥ 20 years) from the 2007–2016 cohorts of the National Health and Nutrition Examination Survey (NHANES) were enrolled. Nutrition Index (NI), Dietary Inflammatory Index (DII), Healthy Eating Index-2020 (HEI-2020), Mediterranean Diet Score (MED), Dietary Approaches to Stop Hypertension (DASH), Dietary Acid Load (DAL), and Composite Dietary Antioxidant Index (CDAI) were calculated based on dietary intake information from the first 24-h recall data. Linear regression models were performed to evaluate the association between different dietary scores and the frailty index (FI). Cox regression models were utilized to identify the associations of dietary indices and frailty with mortality.ResultsFI was significantly higher in participants with CKD compared to the overall population. There was a significant relationship between DII, NI, CDAI, HEI-2020, and MED scores with frailty in CKD patients. Frailty index, DII, NI, and HEI-2020 scores were significantly associated with increased mortality risk in individuals with CKD. The relationship between DII score, NI score, HEI-2020 score, and mortality changed when adjusting for frailty.ConclusionIn individuals with CKD, frailty was associated with DII, NI, CDAI, HEI-2020, and MED scores. A higher FI was significantly associated with increased risk of all-cause mortality. Additionally, higher DII, NI, and lower HEI-2020 scores were related to mortality risk. After adjustment for FI, only a higher NI score (3-year and 5-year mortality) and a lower HEI-2020 score (3-year and 8-year mortality) were associated with higher mortality risk.